Analisa Mekanisme Ragum Penjepit Benda Kerja Menggukan Aktuator Pneumatik pada Mesin Bor - Christof Geraldi Simon; Simon ka'ka; Festo Andre Hardinsi; Formanto Pailing (Science and Education Journal (SICEDU), 2026)
This study aims to determine the magnitude of the effective thrust on the cylinder and the size of the centrifugal force on the drilling machine, and to know the ratio of the effect of effective force and centrifugal force. The method used in this study is to regulate air pressure, starting from 1-6 bar pressure. In Torak Cylinder Effective Push Style, shows a comparison that, the greater the pressure, P (bar) given to the piston cylinder the greater the thrust force value, Fef (N) produced. In the centrifugal force, there is a characteristic that, the smaller the feed speed, V (mm / min) at the spindle rotation, the greater the value of the centrifugal force that occurs in the drilling machine. In the thoracic effective thrust cylinder, and, centrifugal force shows the effect of the relationship between the two forces. This relationship affects the strength of the workpiece stress on the vise. the value of effective thrust force at pressure 2 (Bar) has a value of 883.12 (N) and centrifugal force of 551.301 (N), this shows that the effective thrust produced is greater than the centrifugal force, so it can grip (strong gripping) ) workpiece in vise.